The structure of the offices in the Tropologion of 8–9 cc. And in the Menaia of 9–14 cc. - Nikiforova Aleksandra (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ III. Filologiâ, 2012)
In this article the structure of the services is discussed on the ground of the Greek manuscript Tropologion of 8–9 cc. and Menaia of 9–14 cc., mostly from the libraries of Sinai and Grottaferrata. The research has led to the following fi ndings. The services of the Tropologion of 8–9 cc. were organized by the liturgical order of the chants (στιχηρὰ εἰς Κύριε ἐκέκραξα —κανών — στιχηρὰ εἰς Αἰνεῖτε). Then in the Menaia of 9–11 cc.this structure was changed by another one — genre’s structure (κάθισμα — στιχηρὰ εἰς Κύριε ἐκέκραξα — κανών). In the manuscripts of 12 c. more often you can trace the liturgical order again. This liturgical structure prevailed from 13–14 cc. everywhere on the score of user comfort.